2013
DOI: 10.1186/1532-429x-15-53
|View full text |Cite
|
Sign up to set email alerts
|

Myocardial T1 and T2 mapping at 3 T: reference values, influencing factors and implications

Abstract: BackgroundMyocardial T1 and T2 mapping using cardiovascular magnetic resonance (CMR) are promising to improve tissue characterization and early disease detection. This study aimed at analyzing the feasibility of T1 and T2 mapping at 3 T and providing reference values.MethodsSixty healthy volunteers (30 males/females, each 20 from 20–39 years, 40–59 years, 60–80 years) underwent left-ventricular T1 and T2 mapping in 3 short-axis slices at 3 T. For T2 mapping, 3 single-shot steady-state free precession (SSFP) im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

51
178
15
2

Year Published

2014
2014
2017
2017

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 214 publications
(246 citation statements)
references
References 27 publications
51
178
15
2
Order By: Relevance
“…First, native myocardial T1 values may increase with myocardial edema, fibrosis, infarction, myocarditis, or amyloidosis and are not specific for myocardial inflammation or fibrosis as discussed. Second, T2 mapping was not performed, which would have been an interesting comparison; however, T2 mapping at the present time seems to have a large interindividual variability, 43 which may not have helped significantly in distinguishing between myocardial water from inflammation and that in an expanded extracellular space. Third, postcontrast T1 mapping and extracellular volume quantification were not performed.…”
Section: Limitationsmentioning
confidence: 88%
“…First, native myocardial T1 values may increase with myocardial edema, fibrosis, infarction, myocarditis, or amyloidosis and are not specific for myocardial inflammation or fibrosis as discussed. Second, T2 mapping was not performed, which would have been an interesting comparison; however, T2 mapping at the present time seems to have a large interindividual variability, 43 which may not have helped significantly in distinguishing between myocardial water from inflammation and that in an expanded extracellular space. Third, postcontrast T1 mapping and extracellular volume quantification were not performed.…”
Section: Limitationsmentioning
confidence: 88%
“…27 Both the values of T2 and T1 maps were quantified as previously reported. 28 The qualitative survey implied the exclusion of segments in case of artifacts (eg, caused by susceptibility effects or unintended thoracic motion) or wrong motion correction as described recently. 28 We performed inter-and intraobserver variability analysis.…”
Section: Discussionmentioning
confidence: 99%
“…The results of studies reporting these in various sequences are summarized in Table 2. The true effects of age and sex remain unclear because studies reported discordant associations: T1 values were shown to decrease, 37 increase, 38,39 or have no relationship with age. 26 Similarly, in some studies, females were shown to have higher T1 values, 37,38 whereas others showed no relationship with sex.…”
Section: Normal Rangesmentioning
confidence: 99%